ANALISIS VIRTUAL REALITY PADA GAME VR LOUNGE ROOM: CREED RISE TO GLORY - Revlon Ramadhanti; Dimas Harianto, Rahmat Afdal, Bayu Rahmat Rifdian, Aryani Carissa Puteri, Arifah Kurnia Putri, Isna (ADISAM PUBLISHER, 2024)
Creed: Rise to Glory